2021
DOI: 10.1021/acs.langmuir.0c03138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Exfoliation Efficiency of Quasi-2D Metal Diboride Nanosheets Using Hansen Solubility Parameters

Abstract: Non-van der Waals (non-vdW) solids are emerging sources of two-dimensional (2D) nanosheets that can be produced via liquid-phase exfoliation (LPE), and are beginning to expand our understanding of 2D and quasi-2D materials. Recently, nanosheets formed by LPE processing of bulk metal diborides, a diverse family of layered non-vdW ceramic materials, have been reported. However, detailed knowledge of the exfoliation efficiency of these nanomaterials is lacking, and is important for their effective solution-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…In the top-down approach, the liquid-phase exfoliation method was the most widely used because of its low cost, simple process, and the possibility of further improvement [ 38 , 39 , 40 , 41 ]. In Figure 1 a, the process of exfoliation of h-BN into BNNS and attachment of AgNP on its surface is shown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the top-down approach, the liquid-phase exfoliation method was the most widely used because of its low cost, simple process, and the possibility of further improvement [ 38 , 39 , 40 , 41 ]. In Figure 1 a, the process of exfoliation of h-BN into BNNS and attachment of AgNP on its surface is shown.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the increasing trend from 5:0 to 2:3 was that the BNNS dispersed better due to the addition of IPA, and the ultrasonic cavitation effect of IPA was better than that of H 2 O because the surface tension of IPA (21.7 dyn/cm) was less than that of H 2 O (72.7 dyn/cm) [ 19 ]. A possible explanation for the downward trend of yield after 2:3 was that when IPA:H 2 O = 2:3, the mixed solvent had the best Hansen solubility parameters and the most suitable solvent viscosity, which was beneficial to the dispersion stability of BNNS [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…5(a)]. [83][84][85] This means that boron nanosheets exfoliated in different solvents could show different properties. The functional groups introduced by different organic solvents, such as alcohol, amide, dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), and dimethyl sulfoxide (DMSO), usually exhibit a combination of -O, -OH, -NH 2 , -S]O, alkyl, alkoxy groups, etc., which can lead to broad application but at the same time give rise to difficulty in understanding the individual effect of each functional group.…”
Section: Solvent-derived Functional Groupsmentioning
confidence: 99%
“…Alcohols are efficient solvents that aid in producing boron nanosheets in high yield. 83 Alcohols can tune the band gap of boron nanosheets and borophene due to -OH and -H groups, and the resultant boron nanosheets have been tested for catalysts and optical devices. 21,86 Sun et al prepared boron nanosheets in isopropanol (IPA) and found that the prepared boron nanosheets can effectively catalyze the nitrogen reduction reaction (NRR) with a high faradaic efficiency of 4.04% and a high NH 3 yield of 13.22 mg h À1 mg cat À1 at À0.80 V. 21 The active sites were determined to be the oxidized and H-deactivated B atoms [Fig.…”
Section: Solvent-derived Functional Groupsmentioning
confidence: 99%
“…Based on the HSP approach, we can quantitatively predict solute solubility in a given solvent. Recently, the HSP sphere has been extended to the prediction of particle dispersion in solvents, including carbon, metal oxides, and metal nanoparticles [16][17][18][19][20][21][22][23][24][25][26]. The particle's HSP sphere was based on particle dispersibility experiments of various solvents (high/low dispersibility).…”
Section: Introductionmentioning
confidence: 99%